2008
DOI: 10.1590/s0100-72032008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Valor preditivo do resultado fetal da dopplervelocimetria de ducto venoso entre a 11ª e a 14ª semanas de gestação

Abstract: there is a significant correlation between the alteration of the ductus venosus Doppler velocimetry and the thickness of the nuchal translucency as an ultrasonographic marker for the first trimester of gestation, in the detection of adverse fetal outcome, especially serious malformations. The ductus venosus was able to diminish the false-positive result in comparison to the isolated use of the nuchal translucency thickness, improving considerably the positive predictive value of the test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…FHR and PI are two indices of linear dynamics that can be analyzed in the time and frequency domain. The variability of FHR is influenced by the autonomic nervous system, the fetal body, respiratory movements, baroreflex, and circadian processes (23). A study showed differences in FHR variability in the 1st trimester compared to the 2nd and 3rd trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…FHR and PI are two indices of linear dynamics that can be analyzed in the time and frequency domain. The variability of FHR is influenced by the autonomic nervous system, the fetal body, respiratory movements, baroreflex, and circadian processes (23). A study showed differences in FHR variability in the 1st trimester compared to the 2nd and 3rd trimesters.…”
Section: Discussionmentioning
confidence: 99%